Konflik Kepemimpinan Jamaah Tabligh Di Kota Padang, Sumatera Barat - Muhammad Aqil (Indonesian Center for Religion and Society Studies (InTReSt), 2020)
In da’wah, the Jama'at Tabligh offers a more friendly and polite format of Islam, because in their da'wah they have the principle of ikram al-muslim or glorifying fellow Muslims. In addition they are also known as organizations that avoid the problem of khilafiyah. However, the stigma is violated because they internal conflicts. This study aims to examine the internal conflicts of Tablighi Jamaat. This study focuses on looking the background and the dynamic of conflict that occur in the internal of Jamaah Tabligh. This study uses qualitative methods and conflict triangle theory developed by Johan Galtung. The findings of study indicate the conflict is caused by the problem of leadership or determination of amir. This leadership conflict made the Tabligh Jamaah split into two groups namely the Syuro Alami group and Nizamuddin. The Natural Syuro group made the Muhammadan Mosque in Pondok, Padang as headquarters, while the Nizamuddin group made the Madinatul Munawarah Mosque in the city of Padang as headquarters. At present what happens between the two groups is throwing accusations at each other and berating each other.The conflict caused mutual accusations and verbal abuse between the two groups.